Darwin - Desmond, Adrian; Moore, James R. (Norton, 1992)
"It is like confessing a murder." These are the words Charles Darwin uttered when he revealed to the world what he knew to be true: that humans are descended from headless hermaphrodite squids. How could a wealthy gentleman, a stickler for respectability, attack the foundations of his religion and Anglican society? Authors Adrian Desmond and James Moore, in what has been hailed as the definitive biography of Charles Darwin, not only explain the paradox of the man but bring us the full sweep of Victorian science, theology, and mores. The authors unveil the battle over the mind and soul that raged around the student Darwin as well as his drunken high-life in prostitute-ridden Cambridge. They vividly re-create Darwin's five-year voyage on the Beagle and his struggle to develop his theory of evolution. Then, they follow Darwin through his decades of torment. Fully aware that his ideas could bring ruin and social ostracism to his beloved family, Darwin kept his thoughts secret for twenty years. Seeming to lead an ideal squire's life in rural Kent, he was actually a man "living in Hell," plagued by trembling, vomiting, and violent cramps and confronted by personal tragedy that left him grief-stricken for the rest of his life. But even more than Marx and Freud, this anguished man was to transform the way we see ourselves on this planet. Desmond and Moore's rich, comprehensive, and unparalleled portrait of his life contains a wealth of newly transcribed and unpublished letters, a thorough understanding of all available Darwin research, and ninety photographs, many never published before. Its lively and accessible style makes each chapter as gripping to read as a novel, yet the legitimacy and importance of this seminal work
Keywords: Darwin, Charles <1809-1882>; Darwin, Charles -- 1809-1882; Biologie - Biographies; Naturalists -- England -- Biography; Aufklärung; Darwinismus; Forschungsreise; Evolutionstheorie; Naturphilosophie; Biografie